Effect of Co, Cu, and Zn ions on the bioactivity and antibacterial properties of a borate bioactive glass - dos Santos, Verônica Ribeiro; Campos, Tiago Moreira Bastos; Anselmi, Caroline [UNESP]; Thim, Gilmar Patrocínio; Bottino, Marco C.; Borges, Alexandre Luiz Souto [UNESP]; Trichês, Eliandra de Sousa (Elsevier, 2023)
In this work, our original glycol thermal method was applied to obtain borate bioactive glasses of the 45B5 composition (46.1 B2O3 – 26.9 CaO – 24.4 NaO – 2.6 P2O5, mol%) doped with therapeutic ions Co2+, Cu2+, and Zn2+ aiming toward wound healing applications. The structural analysis performed demonstrated the successful vitreous network obtention, while the apatite mineralization assay exhibited fast conversion into hydroxyapatite (HA, Ca5(PO4)3(OH)). Cell viability findings performed with human keratinocytes revealed an absence of cytotoxicity at concentrations below 0.5 mg/mL at day 1, manifested after 3- and 7-days, demonstrating a time- and dose-dependence in vitro outcome. The inhibition halo assay confirmed the antibacterial activity of all glasses against S. aureus. Considering the set of properties evaluated (i.e., bioactivity, cytocompatibility, and antibacterial activity), the synthesized glasses demonstrate potential for wound healing applications when incorporated into nanofibers, hydrogels, and dermal patches.
Keywords: Biomedical application; Borate bioactive glass; Therapeutic ions